2000
DOI: 10.1023/a:1005178203702
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study examines whether two aspects of mothering--acceptance and consistency of discipline--buffer the effect of divorce stressors on adjustment problems in 678 children, ages 8 to 15, whose families had divorced within the past 2 years. Children reported on divorce stressors; both mothers and children reported on mothering and internalizing and externalizing problems. Multiple regressions indicate that for maternal report of mothering, acceptance interacted with divorce stressors in predicting both dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Following the death of a parent, youth are at an increased risk for a range of mental and physical health problems, and this risk increases when the surviving caregiver’s psychological distress negatively impacts their parenting practices (Kwok et al, 2005; Lutzke, Ayers, Sandler, & Barr, 1997). The provision of warmth/acceptance and effective discipline by the surviving caregiver is a particularly powerful source of protection for youth who experience family disruption or loss (Lin et al, 2004; Wolchik, Wilcox, Tein, & Sandler, 2000). Experimentally increasing effective parenting practices in parentally bereaved families has been found to lower the risk for mental health problems among youth in the short and long term (Kwok et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Following the death of a parent, youth are at an increased risk for a range of mental and physical health problems, and this risk increases when the surviving caregiver’s psychological distress negatively impacts their parenting practices (Kwok et al, 2005; Lutzke, Ayers, Sandler, & Barr, 1997). The provision of warmth/acceptance and effective discipline by the surviving caregiver is a particularly powerful source of protection for youth who experience family disruption or loss (Lin et al, 2004; Wolchik, Wilcox, Tein, & Sandler, 2000). Experimentally increasing effective parenting practices in parentally bereaved families has been found to lower the risk for mental health problems among youth in the short and long term (Kwok et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Items were measured on a three-point scale from (1) like your mother to (3) not like your mother and coded such that higher numbers reflected greater warmth and acceptance. Wolchik et al (2000) has indicated this is a reliable (α = .86) measure of mother-adolescent relationship quality and Wolchik, Wilcox, Tein, and Sandler (2000) reported that the acceptance measure was negatively associated with internalizing problems, r (676) = −.16, p < .001, in children from divorced families. The composite had excellent reliability in the current sample, α = .94.…”
Section: Methodsmentioning
confidence: 99%
“…The parenting quality composite includes four variables: two subscales from the Children’s Report of Parental Behavior Inventory (CRPBI (37, 38), rejection (10 items; alpha=.72) and consistent discipline (8 items; alpha= .83) and two subscales of the Conflict Tactics Scale – Parent Child version II (CTSPC-II) (39), non-violent discipline (4 items; alpha = .76) and psychological aggression (5 items; alpha .77).…”
Section: Methodsmentioning
confidence: 99%